Numerical investigation of the effect on ultimate loading capacity ofdifferent longitudinal reinforcement ratios of a RC portal frame - Karaton, M.; Awla, H. A. (My University, 2018)
In this study, the nonlinear static Pushover analyses of a reinforced concrete portal frame are obtained by using Fiber element method based on displacement. For calculating of cyclic behavior of concrete, the Mander-Priestley-Park model is used. Cyclic behavior of the reinforcement is obtained by using MengottoPinto steel model. Different longitudinal reinforcement ratios are selected for investigating effect on the nonlinear behavior of a portal frame under horizontal forces. Concrete mean strength is 20 MPa and confinement factor is 1.2. The yield strength of reinforcement model is 420 MPa. Obtained results are evaluated with regard to the top displacement-base shear force and top rotation-base moment. The lateral load capacities and the overturning moment capacities obtained from $2^{nd}$, $3^{rd}$, $4^{th}$ and $5^{th} cases were calculated more between 81-200% and 101-286% than 1st case, respectively. As a results, it is determined that the lateral load capacity and the overturning moment capacity increase depending on increasing of longitudinal reinforcement ratio in columns.
Keywords: İnşaat Mühendisliği